The 'agitation bubble 'contrast'' technique: A technique for using intra-peritoneal free air as contrast for the diagnosis of organ perforation. (February 2020) - Ward, James; Samuels, Theophilus; Andorka, Matyas
We report a case using a novel ultrasound technique to diagnose suspected bowel perforation in the presence of peritoneal fluid. Our technique removed the need for radiological confirmation and expedited surgical intervention. This highlights the potential for using this bedside ultrasonographic technique to detect free peritoneal gas in the presence of peritoneal fluid secondary to viscus perforation.